High Prevalence of Esophageal Dysmotility in Asymptomatic Obese Patients. Issue 6 (2014) - Côté-Daigneault, Justin; Leclerc, Pierre; Joubert, Josette; Bouin, Mickael
Abstract : BACKGROUND: Obesity is an important health problem affecting >500 million people worldwide. Esophageal dysmotility is a gastrointestinal pathology associated with obesity; however, its prevalence and characteristics remain unclear. Esophageal dysmotilities have a high prevalence among obese patients regardless of gastrointestinal symptoms. OBJECTIVE: To identify the prevalence of esophageal dysmotility among obese patients. The secondary goals were to characterize these pathologies in obese patients and identify risk factors. METHOD: A prospective study from January 2009 to March 2010 at the University of Montreal Hospital Centre (Montreal, Quebec) was performed. Every patient scheduled for bariatric surgery underwent preoperatory esophageal manometry and was included in the study. Manometry was performed according to a standardized protocol with the following measures: superior esophageal sphincter – coordination and release during deglutition; esophageal body – presence, propagation, length, amplitude and type of esophageal waves of contraction; lower esophageal sphincter – localization, tone, release, intragastic pressure and intraesophageal pressure. All reference values were those used in the digestive motility laboratory. A gastrointestinal symptoms questionnaire was completed on the day manometry was performed. Chart reviews were performed to identify comorbidities and treatments that could influence the results. RESULTS: A total of 53 patients were included (mean [± SD] age 43±10 years; mean body mass index 46±7 kg/m 2 ; 70% female). Esophageal manometry revealed dysmotility in 51% (n=27) of the patients. This dysmotility involved the esophageal body in 74% (n=20) of the patients and the inferior sphincter in 11% (n=3). Mixed dysmotility (body and inferior sphincter) was found in 15% (n=4) of cases. The esophageal body dysmotilities were hypomotility in 85% (n=23) of the patients, either from insignificant waves (74% [n=20]), nonpropagated waves (11% [n=3]) or low-amplitude waves (33% [n=9]). Gastroesophageal symptoms were found in 66% (n=35) of obese patients, including heartburn (66% [n=23]), regurgitation (26% [n=9]), dysphagia (43% [n=15]), chest pain (6% [n=2]) and dyspepsia (26% [n=9]). Among symptomatic patients, 51% (n=18) had normal manometry and 49% (n=17) had abnormal manometry (statistically nonsignificant). Among asymptomatic patients (n=18), 44% (n=8) had normal manometry and 56% (n=10) had abnormal manometry (statistically nonsignificant). Furthermore, no statistical differences were found between the normal manometry group and the abnormal manometry group with regard to medication intake or comorbidities. CONCLUSION: Esophageal dysmotilities had a high prevalence in obese patients. Gastrointestinal symptoms cannot predict the presence of esophageal dysmotility. Hypomotility of the esophageal body is the most common dysmotility, especially from the absence of significant waves.